2018
DOI: 10.1542/peds.2017-4151
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Perspectives on Living With a Sibling With a Chronic Illness

Abstract: The findings are used to outline how changes in family relationships often result in reduced communication and a suppression of healthy siblings' needs. Siblings develop strategies to help them cope with and accept their circumstances, including finding new prosocial ways of meeting their needs in the form of skills and roles they develop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
69
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 46 publications
11
69
0
9
Order By: Relevance
“…Time spent on worrying over their sibling is perceived as a burden in their life, thus underlining the disruptions in their daily lives. This finding supports the few other studies with direct reports on the siblings of chronically ill children and adolescents, which have also found that the siblings were worried and concerned about the well-being of their sibling (Deavin et al, 2018;Wennick & Huus, 2012). However, the present study elaborates on the knowledge of worries in families with type 1 diabetes, as we find that worries are omnipresent and heavy, but also normal for the family members of adolescents with diabetes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Time spent on worrying over their sibling is perceived as a burden in their life, thus underlining the disruptions in their daily lives. This finding supports the few other studies with direct reports on the siblings of chronically ill children and adolescents, which have also found that the siblings were worried and concerned about the well-being of their sibling (Deavin et al, 2018;Wennick & Huus, 2012). However, the present study elaborates on the knowledge of worries in families with type 1 diabetes, as we find that worries are omnipresent and heavy, but also normal for the family members of adolescents with diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…The perspective of siblings of children or youth with type 1 diabetes has, however, not been addressed in many studies (Dougherty, 2015; Loos & Kelly, 2006; de Wit et al., 2020). The few studies focusing on the experience of being a sibling of a child with type 1 diabetes have found that siblings are frequently worried about their ill sibling and experience a need to be watchful and vigilant over their sibling, leading to stress in daily life (Deavin et al., 2018; Herrman, 2010; Wennick & Huus, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Alderfer and colleagues (2010) addressed siblings’ psychosocial adjustment to cancer in a systematic review of literature relating to psychological adjustment, family functioning, social/school functioning, somatic issues, and resilience/growth. Since then, most current reviews focus on experiences/perspectives (Deavin et al, 2018; Dougherty, 2015; Gan et al, 2017; Knecht et al, 2015), followed by psychological adjustment (Incledon et al, 2015; Vermaes et al, 2012) and health-related quality of life (Limbers & Skipper, 2014) of impacted siblings. Family communication among children with epilepsy was recently reviewed as well (O’Toole et al, 2015).…”
Section: Previous Reviews Related To Sibling Adjustment To Childhood mentioning
confidence: 99%
“…The observation that a KKC intervention reduced pain and distress in siblings of children with chronic disease is compelling. Research by Deavin et al 55 has demonstrated that siblings of children with chronic disease may have a suppression of their needs and reduced communication, which highlights the need for approaches to deal with such changes in family dynamics. To this end, KKC's beneficial effect many have important application to the wellbeing of the entire family unit.…”
Section: Study Limitationsmentioning
confidence: 99%